2018
DOI: 10.3390/genes10010004
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Change-Dependent Inherited Epigenetic Response

Abstract: Epigenetic modifications are a mechanism conveying environmental information to subsequent generations via parental germ lines. Research on epigenetic responses to environmental changes in wild mammals has been widely neglected, as well as studies that compare responses to changes in different environmental factors. Here, we focused on the transmission of DNA methylation changes to naive male offspring after paternal exposure to either diet (~40% less protein) or temperature increase (10 °C increased temperatu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…As a consequence, results presented in this issue and elsewhere make clear that this is a time of opportunity for epigenetics as its contours and impact are traced more and more clearly: the epigenome is demonstrated to be very plastic, it changes during development [2], but also, and in a different way, when exposed to external environmental cues. These changes occur sometimes within generations [3] and, in other cases, epigenetic plasticity occurs through generations [4,5], conveying parental effects of very different type (e.g., parental diet or hatchery environment).However, this plastic character of the epigenome makes it also difficult to draw general conclusions on how every epigenotype, genotype and phenotype are interrelated. In this issue, it is shown that phenotypic, and thus potentially gene expression changes, can precede epigenetic changes [3], or that they occur after the initial environmental stimulus [4,5].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…As a consequence, results presented in this issue and elsewhere make clear that this is a time of opportunity for epigenetics as its contours and impact are traced more and more clearly: the epigenome is demonstrated to be very plastic, it changes during development [2], but also, and in a different way, when exposed to external environmental cues. These changes occur sometimes within generations [3] and, in other cases, epigenetic plasticity occurs through generations [4,5], conveying parental effects of very different type (e.g., parental diet or hatchery environment).However, this plastic character of the epigenome makes it also difficult to draw general conclusions on how every epigenotype, genotype and phenotype are interrelated. In this issue, it is shown that phenotypic, and thus potentially gene expression changes, can precede epigenetic changes [3], or that they occur after the initial environmental stimulus [4,5].…”
mentioning
confidence: 99%
“…These changes occur sometimes within generations [3] and, in other cases, epigenetic plasticity occurs through generations [4,5], conveying parental effects of very different type (e.g., parental diet or hatchery environment).However, this plastic character of the epigenome makes it also difficult to draw general conclusions on how every epigenotype, genotype and phenotype are interrelated. In this issue, it is shown that phenotypic, and thus potentially gene expression changes, can precede epigenetic changes [3], or that they occur after the initial environmental stimulus [4,5]. It is also shown that epigenetic modifications can be associated with the magnitude of change in reaction norms of some but not all phenotypic traits [6].…”
mentioning
confidence: 99%
See 3 more Smart Citations